IMPLEMENTASI PERATURAN DAERAH KABUPATEN SIAK NOMOR 1 TAHUN 2012 TENTANG PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DI KABUPATEN SIAK - Rusadi, Sylvina (UIR PRESS, 2017)
Land and building tax is the tax imposed on Earth and buildings. The subject of tax in the United Nations is a person or entity that actually has a thing on the earth and or benefits of the earth and or has the control and or benefit of the building But the reality in the field is still found many phenomena, namely the lack of socialization made by the Revenue Service Financial Management and Regional Assets, the delay in the delivery of Tax Collection Letter of Land and Building Tax to Taxpayers, Supervision conducted by coordinator has not been fully implemented and lack of resources in the submission of Tax Collection Letter of Land Tax and Building Tax and Land and Building Tax collector. In this study to facilitate researchers in conducting research using the type of qualitative research with methods of interviewing, observation and documentation. The results of Implementation of Regional Regulation of Siak Regency No. 1 of 2012 on Land and Rural Land and Urban Tax in Siak Regency (Appointment / Appointment of Coordinator, Supervisor, and Tax Collector), especially in Siak Sub-district has been quite implemented.